Analisa Cacat Timbul pada Material Aluminium Akibat Pemotongan Menggunakan Laser Cutting - Karyadi, Karyadi; Nanda, Rizki Aulia; Suhara, Ade (VOCATECH: Vocational Education and Technology Journal, 2023)
AbstractLaser cutting has been widely used and is growing rapidly in the manufacturing industry, both in the automotive sector and other production fields as needed for fast, precise and accurate cutting processes. Cutting using laser cutting makes it very easy for the production industry to cut steel, aluminum and other materials. However, errors that often occur at this time when input parameters are carried out in the operation of CNC laser cutting often result in defects in the cut material. The purpose of this study was to determine the variation of speed parameters for cutting aluminum alloy type 1050A material with a thickness of 0.8 mm. With these speed variations, it can be seen at what speed the material corresponds to during the laser cutting process. The method in this study was to use an experimental method with variable speeds of 33 mm/s, 55 mm/s and 88 mm/s, then look at the defects that arise and make measurements arising from the flatness of the plate using a digital dial indicator. The results of this study showed that the highest defects were on the average of sections A3 and B3 of 0.012 mm with a plate diameter of 50.2 and 45.2 mm with an aluminum plate thickness of 0.8 mm. At a speed of 33 mm/s, it can be concluded that the appearance of these defects is very small, ranging from 0.004 mm-0.008 mm.Keywords:Arise Defects; Aluminum Alloy; Laser Cutting. AbstrakPemotongan laser cutting telah banyak digunakan dan berkembang pesat di dunia industri manufaktur, baik di bidang otomotif maupun bidang produksi lainya sebagaimana dibutuhkan untuk proses pemotongan secara cepat, tepat dan akurat. Pemotongan menggunakan laser cutting sangat memudahkan bagi para industri produksi dalam memotong sebuah material baja aluminium dan material-material lainnya. Namun kesalahan yang sering terjadi pada saat ini apabila input parameter yang dilakukan dalam pengoperasian CNC laser cutting sering terjadi kecacatan pada material hasil potongan tersebut. Tujuan dari penelitian ini adalah dengan menentukan variasi parameter kecepatan terhadap pemotongan material aluminium alloy tipe 1050A ketebalan 0,8 mm. Dengan variasi kecepatan tersebut dapat dilihat pada kecepatan berapa yang sesuai dengan material tersebut pada saat proses laser cutting. Metode pada penelitian ini adalah menggunakan metode eksperimen dengan variable kecepatan sebesar 33 mm/s, 55 mm/s dan 88 mm/s, selanjutnya melihat cacat timbul dan melakukan pengukuran yang timbul dari kerataan plat menggunakan dial indikator digital. Hasil penelitian ini menunjukkan cacat timbul tertinggi pada rata-rata bagian A3 dan B3 sebesar 0,012 mm dengan diameter plat 50,2 dan 45,2 mm pada ketebalan plat aluminium 0,8 mm. Pada kecepatan 33 mm/s dapat disimpulkan bahwa timbulnya cacat tersebut sangat kecil berkisar antara 0,004 mm-0,008 mm.Kata Kunci:            Aluminium Alloy; Cacat Timbul; Laser Cutting